Successful Endovascular Management of a Massive Hemoptysis due to a Rare Oncological Giant Pulmonary Artery Pseudoaneurysm - Borzelli, Antonio; Amodio, Francesco; Cavaglià, Enrico; Giurazza, Francesco; Corvino, Fabio; Corvino, Antonio; Pane, Francesco; Coppola, Milena; de Magistris, Giuseppe; Cangiano, Gianluca; Niola, Raffaella (Journal of Endovascular Resuscitation and Trauma Management, 2022)
Massive hemoptysis represents a distressing and life-threatening condition: 95% of cases originate from the bronchial artery system, with pulmonary arteries accounting for 6%–11% of cases. The most common etiology of hemoptysis from the pulmonary artery system is represented by pulmonary artery pseudoaneurysms (PAPs). PAPs are defined as the focal dilation of a pulmonary artery branch, involving only the adventice, with a higher risk of rupture than a true aneurysm. It constitutes a rare finding, often underdiagnosed by radiologists. However, PAPs can be life-threatening if undiagnosed due to a high mortality rate (50%). They frequently occur in patients affected by erosive inflammatory processes and necrotising infections of the lung or heart, but other etiological factors include trauma, vasculitis, neoplasia, pulmonary hypertension and Hughes–Stovin Syndrome. PAPs due to oncologic etiologies are rare. Among oncologic etiologies, the most frequent are represented by primary lung cancer rather than metastases. Today, CT angiography represents the imaging modality of choice; not only to establish diagnosis, but if performed with an appropriate timing of intravenous contrast, it also helps to plan therapy with an endovascular approach. In fact, endovascular treatment is the preferred therapeutic approach in managing hemoptysis due to PAPs, since a surgical approach is associated with a high risk of morbidity and mortality, especially in patients who are poor surgical candidates. In this article we report the case of massive hemoptysis due to an unusual giant PAP of the posterior lower branch of the right pulmonary artery, in a patient affected by pulmonary colliquated and confluent metastases, successfully treated by endovascular embolisation.